PERAN KYAI DALAM PERGESERAN PERILAKU POLITIK MASSA NU DI KABUPATEN BANYUMAS PADA PEMILIHAN PRESIDEN 2024 - Chanifia Izza Millata; Khairurrizqo Khairurrizqo; Titis Perdani (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study aims to analyze the shift in the political behavior of Nahdlatul Ulama (NU) members in Banyumas Regency during the 2024 Presidential Election and to examine the role of kyai in this process. This research is motivated by the fragmentation of political preferences among NU members in the 2024 presidential election, indicating that political support was no longer consolidated toward a single political force. This study employed a qualitative method with a case study approach. Data were collected through literature review, in-depth interviews, and observations involving kyai, santri, and NU members in Banyumas Regency. Data analysis used the interactive analysis model of Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings show that the political preferences of NU members in Banyumas tend to be fragmented and are no longer fully determined by organizational affiliation. The role of kyai remains relevant as charismatic figures; however, their role has shifted from determinant actors to actors who merely influence political preferences. This influence is also associated with political signaling from the Central Board of Nahdlatul Ulama (PBNU), which is interpreted differently by NU members at the local level. In addition, the relatively egalitarian socio-cultural characteristics of Banyumas society, along with the increasing rational considerations of voters, contribute to the weakening of kyai’s determinative role in shaping political choices. These findings demonstrate the novelty that religious authority is no longer dominant in determining political behavior, but rather operates contextually and interacts with rational factors as well as local political dynamics.